A comparative study of wooden house construction in Jeollanamdo in South Korea and Okinawa Prefecture in Japan following World War II. Issue 2 (4th March 2021) - Gondo, Tomoyuki; Kim, Sunwook
ABSTRACT: This paper compares the changes in the production of wooden houses after WWII in Jeollanamdo in South Korea and Okinawa Prefecture in Japan. This study finds that wooden house production shares the following similarities in both locations: (1) traditional wooden post and beam houses were constructed by local carpenters using local wood; (2) following WWII, houses came to be constructed of concrete blocks or reinforced concrete instead of wood; (3) in the 1980s and the 1990s, the number of light-frame wood houses increased; and (4) in the 1990s and the 2000s, wooden post and beam houses increased. This paper examines two case studies conducted in Jeollanamdo and Okinawa Prefecture, respectively, to better understand the current status of wooden post and beam house construction. Jeollanamdo initiated a Happiness Village Project in 2007. This initiative increased the construction of post and beam houses by addressing the shortage of experienced contractors. Starting in the 1990s in Okinawa, the adoption of precut lumber increased the construction post and beam houses, negating the need for traditionally skilled carpenters. However, due to there being few experienced contractors, factories producing precut lumber supported small-scale contractors through training and additional services. Chemical modification of respiratory complex I. The author focuses on structural features of the binding pocket of quinone/inhibitors in complex I. Graphical abstract: uf0001